The practice of sustainable home cooking – a fascinating philosophical perspective - Salgado, Diana; Verkerk, Maarten J. (Frontiers in Sustainable Food Systems, 2022)
In this article, we explore the practice of sustainable home cooking from a philosophical perspective. First, we apply the theory of modal aspects developed by the philosopher Dooyeweerd to understand the different aspects in which the practice of sustainable home cooking functions. Second, we apply the practice approach to understand the dynamics of sustainable home cooking. We make a distinction between the sub practices ‘preparing a meal’ and ‘eating a dish’. These sub practices are analyzed from a specific practice approach: the Triple I model, i.e., identity and intrinsic values, interests of stakeholders, and ideals and basic beliefs.